Ethics of Public Administration in the Era of Technology Disruption and Government Innovation - Lia Muliawaty; Dyah Bayu Framesthi (Department of Government Studies Universitas Muhammadiyah Makassar, 2020)
Good public administration services are the main thing in running a quality government. Therefore, ethics is a major part of maintaining the quality of public administration services, especially in the era of Industry 4.0 which needs to also apply ethics in using technology. The purpose of this study is to examine the formation and implementation of ethics in public administration in the era of government innovation disruption due to technological development and disruption. This research uses a qualitative approach with descriptive analysis method which is sourced from various literature both primary and secondary, then an analysis of the various literature is carried out. Descriptive analysis results show that technology has become an indispensable need in government, in various fields and activities. Where, the disruption of the technology also impacts on various government innovations that really need ethics, especially on public services to avoid mal-administration. The impact of this research is knowledge of the importance of awareness of implementing ethics in public administration services in the era of technological disruption to improve the quality of government services.